Fractionation of sulfur isotopes by Desulfovibrio vulgaris mutants lacking hydrogenases or type I tetraheme cytochrome c3 - Sim, Min Sub; Wang, David T.; Zane, Grant M.; Wall, Judy D.; Bosak, Tanja; Ono, Shuhei (Frontiers in Microbiology, 2013)
The sulfur isotope effect produced by sulfate reducing microbes is commonly used to trace biogeochemical cycles of sulfur and carbon in aquatic and sedimentary environments. To test the contribution of intracellular coupling between carbon and sulfur metabolisms to the overall magnitude of the sulfur isotope effect, this study compared sulfur isotope fractionations by mutants of Desulfovibrio vulgaris Hildenborough. We tested mutant strains lacking one or two periplasmic (Hyd, Hyn-1, Hyn-2, and Hys) or cytoplasmic hydrogenases (Ech and CooL), and a mutant lacking type I tetraheme cytochrome (TpI-c3). In batch culture, wild-type D. vulgaris and its hydrogenase mutants had comparable growth kinetics and produce the same sulfur isotope effects. This is consistent with the reported redundancy of hydrogenases in D. vulgaris. However, the TpI-c3 mutant (ΔcycA) exhibited slower growth and sulfate reduction rates in batch culture, and produced more H2 and an approximately 50% larger sulfur isotope effect, compared to the wild type. The magnitude of sulfur isotope fractionation in the CycA deletion strain, thus, increased due to the disrupted coupling of the carbon oxidation and sulfate reduction pathways. In continuous culture, wild-type D. vulgaris and the CycA mutant produced similar sulfur isotope effects, underscoring the influence of environmental conditions on the relative contribution of hydrogen cycling to the electron transport. The large sulfur isotope effects associated with the non-ideal stoichiometry of sulfate reduction in this study imply that simultaneous fermentation and sulfate reduction may be responsible for some of the large naturally-occurring sulfur isotope effects. Overall, mutant strains provide a powerful tool to test the effect of specific redox proteins and pathways on sulfur isotope fractionation.